2004
DOI: 10.1055/s-2004-825592
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Thermal Stability and Carbonyl Addition Reactions of 2,5-Difluorophenyl Lithium and 2,5-Difluorophenyl Grignard

Abstract: The generation of 2,5-difluorophenyl lithium 2 by lithiation of 1,4-difluorobenzene with BuLi in THF, with and without amine additives, has been surveyed. Thermal stability data of the organolithium species 2 generated with and without TMEDA were determined and the synthetic utility of 2 in the addition to aldehyde and ketone electrophiles is described. Preparation and stability of the corresponding organomagnesium reagent 1, generated by bromine-magnesium exchange of 1-bromo-2,5-difluorobenzene with isopropyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…We were concerned that the 2,5-difluorophenyl Grignard reagent might be unstable and would generate the corresponding benzyne. , A study of the formation and stability of this reagent, however, showed that it was fully formed within 1 h and is stable for up to 4 h at <−10 °C. While we were unconcerned with the stereochemical outcome of the addition reaction, it is interesting to note that transmetalation of the Grignard reagent with cerium resulted in a higher proportion of equatorial attack, leading to a 1:1.9 ratio of 4a and 4b , respectively…”
Section: Resultsmentioning
confidence: 99%
“…We were concerned that the 2,5-difluorophenyl Grignard reagent might be unstable and would generate the corresponding benzyne. , A study of the formation and stability of this reagent, however, showed that it was fully formed within 1 h and is stable for up to 4 h at <−10 °C. While we were unconcerned with the stereochemical outcome of the addition reaction, it is interesting to note that transmetalation of the Grignard reagent with cerium resulted in a higher proportion of equatorial attack, leading to a 1:1.9 ratio of 4a and 4b , respectively…”
Section: Resultsmentioning
confidence: 99%
“…This practical through process afforded 15 in 83% yield over four steps. Grignard reagent 16 was then prepared through a halogen–metal exchange upon treatment of 1,4-difluoro-2-bromobenzene with i -PrMgCl or turbo Grignard ( i -PrMgCl/LiCl) in THF or toluene . Treatment of amide 15 with 16 gave the desired ketone 17 , which was isolated from heptane in 78% yield.…”
mentioning
confidence: 99%
“…It was found that ortholithiation of 1,2-difluorobenzene was possible using n -hexyllithium at −65 °C; however, rapid decomposition was observed at temperatures above −50 °C …”
mentioning
confidence: 99%